2022
DOI: 10.1371/journal.pone.0274490
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal shedding of coronavirus by straw-colored fruit bats at urban roosts in Africa

Abstract: The straw-colored fruit bat ( Eidolon helvum ) is a pteropodid whose conservation is crucial for maintaining functional connectivity of plant populations in tropical Africa. Land conversion has pushed this species to adapt to roosting in urban centers across its range. These colonies often host millions of individuals, creating intensive human-bat contact interfaces that could facilitate the spillover of coronaviruses shed by these bats. A better understanding of coronavirus dynamics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
3
5
0
Order By: Relevance
“…We also confirmed that juvenile and subadult bats are infected at higher rates than adult bats, as previously reported [ 19 , 53 ]. This was observed in all species for which sufficient juvenile and/or subadults have been included.…”
Section: Discussionsupporting
confidence: 92%
“…We also confirmed that juvenile and subadult bats are infected at higher rates than adult bats, as previously reported [ 19 , 53 ]. This was observed in all species for which sufficient juvenile and/or subadults have been included.…”
Section: Discussionsupporting
confidence: 92%
“…Further, careful attention to viral dynamics throughout the reproductive cycle in a wider variety of bat host species will help identify periods of increased zoonotic spillover risk to humans, since spillover is often associated with pulses of viral excretion in reservoir hosts [6,12,24,25]. Our work is congruent with recent, related studies that indicate the pup weaning period, not necessarily pregnancy or lactation periods, may be most strongly associated with viral shedding in bats [20,89]. Consideration of the interplay between reproductive biology and host defenses will improve our understanding of virus-host dynamics and ultimately bolster our ability to prevent spillover from bats and other important wildlife hosts of viral pathogens.…”
Section: Discussionsupporting
confidence: 85%
“…Seasonality of bat-associated viral outbreaks may be linked to features of bat life history and reproductive ecology, such as metapopulation structure, migration, or synchronous birthing [12,13,[18][19][20]. For example, some bat species form large maternity colonies which increase local population density and intraspecific contact rates, thus increasing the potential for pathogen transmission and providing an ideal context for researchers to conduct viral sampling [18,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Life-history parameters such as reproductive cycles influence virus infection dynamics, and gradual loss of maternal immunity among young bats increases the number of susceptible individuals [14,15]. Population estimates and identifying the proportion of naive individuals with longitudinal data are thus important to understand viral maintenance and infection dynamics; a recent paper published after our meta-analysis cut-off date that details longitudinal sampling for coronaviruses in Eidolon helvum illustrates the strength of this approach [46]. We encourage gathering more comprehensive data on target species and provide a data collection framework (figure 2; electronic supplementary material, figure S9) that will facilitate context-specific goals and priority establishment for bat-virus studies.…”
Section: (B) Species and Guilds Of Bats Sampled And Their Numbersmentioning
confidence: 99%